Dynamic Interaction of High-Voltage Power Transformer Bushings, Turrets, and Tanks. Issue 1 (February 2018) - Ma, Guo-Liang; Xie, Qiang; Whittaker, Andrew
High-voltage (HV) bushings are attached to a power transformer tank either directly or indirectly via turrets. Turrets are used to achieve electrical performance requirements, but their potential impact on the seismic performance of the supported bushings has not been considered. Earthquake simulator testing and finite-element analysis were used to quantify the amplification of ground shaking through tanks (220- and 500-kV) and turrets to the points of attachment of roof- and sidewall-supported bushings. Substantial amplification of motion was seen in both physical experiments and numerical simulations. Sample bracing schemes external to the transformer tank were investigated to potentially reduce the motions experienced by the bushings. Bushing tip displacements were reduced in all stiffening cases studied, but the outcomes for bending moment at the bushing-turret connection were mixed, with no change in some cases and significant reductions in others. The physical and numerical studies described in this paper make clear the importance of dynamic interaction of bushings, turrets, and the power transformer tank. The methods currently used to address the amplification of input motion from the base of a tank to the points of attachment of its bushing are inadequate. The seismic design of HV power transformer tanks and turrets should be supported by finite-element analysis of validated models to avoid dynamic interaction in the bushing-turret-tank system, to minimize seismic demand on the transformer bushings, and to minimize the risk of substation damage in earthquakes.